Insights into relationships between body mass, composition and bone: findings in elite rugby players - Hind, K.; Gannon, L.; Brightmore, A.; Beck, B. (Journal of Clinical Densitometry, 2015)
Recent reports indicate that bone strength is not proportional to body weight in obese populations. Elite rugby players have a similar body mass index (BMI) to obese individuals but differ markedly with low body fat, high lean mass, and frequent skeletal exposure to loading through weight-bearing exercise. The purpose of this study was to determine relationships between body weight, composition, and bone strength in male rugby players characterized by high BMI and high lean mass. Fifty-two elite male rugby players and 32 nonathletic, age-matched controls differing in BMI (30.2 ± 3.2 vs 24.1 ± 2.1 kg/m2; p = 0.02) received 1 total body and one total hip dual-energy X-ray absorptiometry scan. Hip structural analysis of the proximal femur was used to determine bone mineral density (BMD) and cross-sectional bone geometry. Multiple linear regression was computed to identify independent variables associated with total hip and femoral neck BMD and hip structural analysis-derived bone geometry parameters. Analysis of covariance was used to explore differences between groups. Further comparisons between groups were performed after normalizing parameters to body weight and to lean mass. There was a trend for a positive fat-bone relationship in rugby players, and a negative relationship in controls, although neither reached statistical significance. Correlations with lean mass were stronger for bone geometry (r2: 0.408-0.520) than for BMD (r2: 0.267-0.293). Relative to body weight, BMD was 6.7% lower in rugby players than controls (p < 0.05). Rugby players were heavier than controls, with greater lean mass and BMD (p < 0.01). Relative to lean mass, BMD was 10%-14.3% lower in rugby players (p < 0.001). All bone geometry measures except cross-sectional area were proportional to body weight and lean mass. To conclude, BMD in elite rugby players was reduced in proportion to body weight and lean mass. However, their superior bone geometry suggests that overall bone strength may be adequate for loading demands. Fat-bone interactions in athletes engaged in high-impact sports require further exploration.